Associations between low‐value care treatments and patient‐centered outcomes of people with dementia: A cross‐sectional analysis. (31st December 2021) - Platen, Moritz; Raedke, Anika; Wucherer, Diana; Thyrian, Jochen René; Mohr, Wiebke; Scharf, Annelie; Mühlichen, Franka; Hoffmann, Wolfgang; Michalowsky, Bernhard
Abstract: Background: Rapidly increasing healthcare expenditures are a global healthcare challenge. Parts of these costs are caused by an overtreatment of patients or low‐value care (LvC), which is defined as care unlikely to provide a benefit to the patient or likely to provide harm. However, there is currently a lack of evidence about the prevalence of LvC and its association with patient‐reported outcomes in people living with dementia (PwD). Method: The analysis was based on the baseline data of the DelpHi‐trial, including 516 community‐dwelling PwD. LvC were identified by a systematic review of dementia‐specific evidence‐based guidelines, "do not do" recommendations of initiatives, like "Choosing Wiseley", and lists of inappropriate medication for the elderly. The association of LvC treatments with health‐related quality of life (HRQol), assessed by using the SF‐12 and the Quality of life in Alzheimer´s diseases, and hospitalization were analyzed using multiple regression models. Result: The study revealed that 159 PwD (31 %) received at least one LvC treatment. They had, on average, less cognitive impairment and less functional impairment than those without LvC. PwD who received LvC had a lower quality of life (b=‐0.08; CI 95% ‐0.14 – ‐0.02) and were more likely to be hospitalized (OR=2.11; CI 95% 1.30 – 3.41). The lower HRQol was attributed to the measured sedatives and hypnotics (B=‐0.21; CI95% ‐0.34 – ‐0.08). The higher odds for hospitalization could be caused by antidepressants (OR=2.86; CI95% 1.10 – 7.46) and antihypertensive drugs (OR=4.09; CI95% 1.20 – 13.92). Conclusion: LvC could reduce patients' HRQoL and increase the risk of hospitalization. More research is needed to evaluate if innovative approaches, like digital health applications, are useful to identify and reduce LvC within primary care and if this could improve PwD HRQoL and reduce hospitalizations.